2020
DOI: 10.1016/j.foodqual.2020.103916
|View full text |Cite
|
Sign up to set email alerts
|

A values–beliefs–attitude model of local food consumption: An empirical study in China and Denmark

Abstract: This is a self-archived -parallel published version of this article in the publication archive of the University of Vaasa. It might differ from the original.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 69 publications
4
59
0
3
Order By: Relevance
“…This study provides a more comprehensive view of the impact of the COVID-19 pandemic on consumers' attitudes and behavior. The risk of infection and the possibility of having the disease led individuals to be more inclined toward locavorism, which in turn has a strong impact on developing a positive ATT toward LPF (Zhang et al, 2020). Consistent with previous studies on health awareness, the results showed that when individuals are concerned about their health, the ATT toward local food products increases positively (Singh and Verma, 2017).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study provides a more comprehensive view of the impact of the COVID-19 pandemic on consumers' attitudes and behavior. The risk of infection and the possibility of having the disease led individuals to be more inclined toward locavorism, which in turn has a strong impact on developing a positive ATT toward LPF (Zhang et al, 2020). Consistent with previous studies on health awareness, the results showed that when individuals are concerned about their health, the ATT toward local food products increases positively (Singh and Verma, 2017).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, individuals consume local products because they are convinced that they favor the economic development of local communities and that the production systems are safer, more transparent (Meyerding et al, 2019) and more sustainable (Schmitt et al, 2017). Although research on locavorism is not abundant, some recent studies have found evidence showing that an attraction to the locavore stance positively influences consumers' attitudes when buying local foods in countries like China and Denmark (Zhang et al, 2020).…”
Section: Locavorismmentioning
confidence: 99%
See 1 more Smart Citation
“…A local FSC is one of the most popular solutions that have been mentioned by academics and governments. The main barriers to consuming local food are higher prices, accessibility, and availability [71]. From the government side, a subsidy to retailers or farmers would increase the competitiveness of the local foods.…”
Section: Promotion Of Local Food Consumptionmentioning
confidence: 99%
“…From the government side, a subsidy to retailers or farmers would increase the competitiveness of the local foods. The U.S. Department of Agriculture has invested more than USD 20 million each year since 2017 to promote local food consumption [71]. Moreover, food producers and retailers also need to label local foods to ensure they are easily visible among the thousands of food products in the supermarkets.…”
Section: Promotion Of Local Food Consumptionmentioning
confidence: 99%